2017
DOI: 10.1155/2017/6570808
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of C-Reactive Protein/Albumin is a Novel Inflammatory Predictor of Overall Survival in Cisplatin-Based Treated Patients with Metastatic Nasopharyngeal Carcinoma

Abstract: The C-reactive protein/albumin (CRP/Alb) ratio has been recently identified as a prognostic factor in various cancers, whereas its role remains unclear in metastatic nasopharyngeal carcinoma (NPC). The current study retrospectively analyzed 148 patients with metastatic NPC who underwent cisplatin-based chemotherapy and further evaluated the prognostic value of the CRP/Alb ratio and its association with clinical characteristics in these patients. The optimal cut-off value was 0.189 for the CRP/Alb ratio. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 49 publications
2
47
0
1
Order By: Relevance
“…Although CRP and ALB have good prognostic signi cance for AECOPD patients, the early in ammatory response and nutritional status of the body may not change in equal proportion. Therefore, CRP/ALB ratio has been recently identi ed as a valuable predictor of prognosis in patients with various diseases such as tumor and sepsis, 10,15,16 whereas its prognostic role remains unclear in AECOPD patients with HF. In our study, we showed that CRP/ALB ratio was signi cantly higher in non-survivors than in survivors (P< 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Although CRP and ALB have good prognostic signi cance for AECOPD patients, the early in ammatory response and nutritional status of the body may not change in equal proportion. Therefore, CRP/ALB ratio has been recently identi ed as a valuable predictor of prognosis in patients with various diseases such as tumor and sepsis, 10,15,16 whereas its prognostic role remains unclear in AECOPD patients with HF. In our study, we showed that CRP/ALB ratio was signi cantly higher in non-survivors than in survivors (P< 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…There is strong linkage between inflammation and cancer. As we know, serum CRP is a very sensitive indicator of systemic inflammatory response, and NLR is other index of systemic inflammation [ 16 ]. Previous studies have shown that serum CRP and NLR are predictors of prognosis in several cancers, including EC [ 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another inflammation-related biomarker, the blood C-reactive protein (CRP)-to-albumin ratio (CAR), has also been reported to be a good prognostic factor in various cancer types (9)(10)(11)(12)(13)(14)(15). In some of these studies, CAR and NLR were assessed simultaneously, and both of them were reported to be prognostic factors for OS in patients with operable non-small cell lung cancer and those with unresectable metastatic colorectal cancer (9,11).…”
Section: The Prognostic Utility Of the Pretreatment Blood Neutrophiltmentioning
confidence: 99%
“…In some of these studies, CAR and NLR were assessed simultaneously, and both of them were reported to be prognostic factors for OS in patients with operable non-small cell lung cancer and those with unresectable metastatic colorectal cancer (9,11). However, in other types of cancer (metastatic nasopharyngeal carcinoma, surgical renal cell carcinoma, surgical gastric cancer), CAR was found to be an independent prognostic factor for OS, while NLR was not (10,12,13). As for MPM, as far as we are aware, only one study reported the prognostic utility of CAR (16), and no previous study has compared the prognostic utility of CAR and NLR.…”
Section: The Prognostic Utility Of the Pretreatment Blood Neutrophiltmentioning
confidence: 99%